KILKA UWAG DOTYCZĄCYCH POWOŁYWANIA CZŁONKÓW ZARZĄDU SPÓŁEK KAPITAŁOWYCH - Gawrysiak-Zabłocka, Aleksandra (Zeszyty Prawnicze, 2016)
SOME REMARKS ON THE APPOINTMENT OF COMPANY DIRECTORS Summary The article discusses selected issues concerning the appointment of company directors. In the first part the focus is on the practical application of Art. 18 of the Polish Code of Commercial Companies (Kodeks spółek handlowych, KSH), which provides that only natural persons having full legal capacity and not convicted for crimes or offences mentioned in that provision can be members of a company’s board of managers. In the light of the inconsistent rulings handed down by the Polish Supreme Court (Sąd Najwyższy) it is not clear whether the registering court, which has information available from the National Criminal Register (Krajowy Rejestr Skazanych), may refuse to enter a resolution which has been passed at a shareholders’ meeting but is in breach of the law. In my opinion, the first premise in the ruling handed down by seven Supreme Court judges on 18 September 2013 (case III CZP 13/13) is flawed. Not only does it contradict the Supreme Court decision of 24 July 2013 (case III CNP 1/13), but also its consequences can hardly be reconciled with the consequences of the second premise. In the second part of the study I use the provision on the composition of a brokerage board to show that specific regulations may prove ineffective if they only give cursory attention to an issue, with no reference to what is stipulated by the KSH.